Use of Ultrathin Bronchoscope on a Need Basis Improves Diagnostic Yield of Difficult-to-Approach Pulmonary Lesions - Nishii, Yoichi; Nakamura, Yuki; Fujiwara, Kentaro; Ito, Kentaro; Sakaguchi, Tadashi; Suzuki, Yuta; Furuhashi, Kazuki; Kobayashi, Tetsu; Yasuma, Taro; D'Alessandro-Gabazza, Corina N.; Gabazza, Esteban C.; Asano, Fumihiro; et al. (Frontiers in Medicine, 2020)
There are cases of peripheral lung nodules difficult to approach despite using ancillary diagnostic devices during multimodal bronchoscopy. The use of ultrathin bronchoscopes has shown superiority over standard thin bronchoscopes. We retrospectively evaluated whether substitution of thin-bronchoscope by the ultrathin device during multimodal bronchoscopy improves lesion ultrasound visualization and diagnostic yield in patients with difficult-to-approach pulmonary lesions. The study comprised 44 out of 338 patients that underwent multimodal bronchoscopy at Matsusaka Municipal Hospital. The thin-bronchoscope with an external diameter of 4-mm was substituted by the ultrathin-bronchoscope with an external diameter of 3-mm when the radial endobronchial ultrasound showed that the probe position was not within the target lesion. The median diameter of the pulmonary tumors was 17.5 mm (range: 6.0 – 5.2.0 mm). The endobronchial ultrasound showed the probe's position adjacent to the lesion in 12 cases and no visible lesion in 32 cases using a thin-bronchoscope. However, the endobronchial ultrasound views changed from adjacent to the lesion to within the lesion in 9 cases, from no visible lesion to within the lesion in 17 cases, and from no visible lesion to adjacent to the lesion in 9 cases after bronchoscope substitution. After substitution, the diagnostic yield was 80.8% in cases with the radial probe within the target lesion, 72.7% in cases with the probe adjacent to the target lesion, and 0% in cases with no visible lesion. The overall diagnostic yield was 65.9% after bronchoscope substitution. The substitution of the thin bronchoscope by the ultrathin device on a need basis improves the position of the radial endobronchial ultrasound probe and the diagnostic yield of pulmonary lesions during multimodal diagnostic bronchoscopy.